Aspectos teóricos de los modelos fonológicos - Hernando Cuadrado, Luis Alberto (Dicenda. Estudios de lengua y literatura españolas, 2008)
Though the concept of phonology is in latent state from the Antiquity with the discovery and the use of the syllabic writing and the distinction between sound and symbol, and in more nearby times there are important events like the adoption of the term phoneme, the impulse of the universal systems of phonetic transcription and other more or less decisive finds, is in the decade of the thirties of the XXth century when the phonology receives finally the consideration of linguistic discipline with own entity, especially with the works of the Linguistic Circle of Prague. From the model of the functional phonology others happened like that of the generative classic one, that of he generative natural one and the natural, that of the autosegmental, that of the lexical one, that of the prosodic one and that of the optimality theory, principally. If in the functional phonology the most relevant aspect was the relative one to the representations and in the generative classic one the center of interest gravitates on the rules, in the posterior models a certain sway is produced between both attitudes on the base of new suppositions, up to his displacement towards the constraints with the optimality theory.